Non-Canonical Mechanisms Regulating Hypoxia-Inducible Factor 1 Alpha in Cancer - Iommarini, Luisa; Porcelli, Anna Maria; Gasparre, Giuseppe; Kurelac, Ivana (Frontiers in Oncology, 2017)
Hypoxia inducible factor 1 alpha (HIF-1) orchestrates cellular adaptation to low oxygen and nutrient deprived environment and drives progression to malignancy in human solid cancers. Its canonical regulation involves prolyl hydroxylases (PHDs), which in normoxia induce degradation, whereas in hypoxia allow stabilization of HIF-1. However, in certain circumstances HIF-1 regulation goes beyond the actual external oxygen levels and involves PHD-independent mechanisms. Here we gather and discuss the evidence on the non-canonical HIF-1 regulation, focusing in particular on the consequences of mitochondrial respiratory complexes damage on stabilization of this pleiotropic transcription factor.